Religião, educação e política na trajetória intelectual do padre Paul-Eugène Charbonneau / Religion, education and politics in the intellectual trajectory of priest Paul-Eugène Charbonneau - Santos, Bárbara da Silva; Orlando, Evelyn de Almeida (Revista de História e Historiografia da Educação, 2019)
Este artigo aborda aspectos da trajetória do padre canadense Paul-Eugène Charbonneau, que atuou no Brasil, a partir de diferentes campos, intervindo na configuração da sociedade brasileira por meio da educação e da cultura. Com base na produção escrita deste intelectual, buscamos, neste artigo, apontar como a religião, a política e a educação estiveram presentes na trajetória intelectual do padre Charbonneau. Os conceitos de intelectual e elites culturais de Sirinelli (1998; 2003) e de trajetória, capital social, capital cultural e de campo de Bourdieu (2000; 2003; 2004; 2007) embasaram o aporte teórico do texto. Pensar a trajetória do intelectual Charbonneau permeada pelos campos da religião, educação e política, é perceber que a sua produção escrita não estava associada apenas à disseminação dos saberes educacionais com princípios católicos, mas trouxe discussões sobre o contexto político da época, ora trazendo elementos cristãos, ora incorporando o ator do político e cidadão brasileiro que se tornou. *** This article approaches trajectory aspects of Canadian priest Paul-Eugène Charbonneau, who worked in Brazil, from different fields, intervening in the configuration of Brazilian society through education and culture. Based on the written production of this intellectual, we seek to point out how religion, politics and education were present in the intellectual trajectory of Father Charbonneau. Concepts like intellectual and cultural elites, by Sirinelli (1998, 2003), and Bourdieu’s trajectory, social capital, cultural capital and field (2000, 2003, 2004, 2007) were the theoretical basis of this text. To think about the trajectory of intellectual Charbonneau, permeated by the fields of religion, education and politics, is to realize that his written production was not only associated with the dissemination of educational knowledge with Catholic principles, but brought discussions about the political context of the time, sometimes bringing Christian elements, sometimes incorporating the actor of the politician and Brazilian citizen hia had become.